Behavioral intention pengguna smart home menggunakan UTAUT 2: Studi di Citraraya Tangerang - Kuarizmi, Arief Betta; Padmalia, Metta; Teofilus, Teofilus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
Real estate is experiencing changes due to technological advances. Smart homes have become the flagship product each other among housing developers. By using the UTAUT 2 model, the aim of this research is to investigate the variables that influence the behavioral intentions of smart home users. Quantitative studies were carried out through distributing questionnaires online. The results of the study revealed that social influence and facilitating conditions have an influence on behavioral intention. On the other hand, behavioral intention is not affected by performance expectancy, effort expectancy, hedonic motivation, habit, or price value. In addition, facilitating, habit, and behavioral intention have a positive impact on usage behavior.. It is hoped that this empirical knowledge will increase sales and collect good data to understand and apply this phenomenon.